Strategi Kepemimpinan dalam Meningkatkan Etos Kerja Pegawai di BAZNAS Provinsi Sumatera Barat - Yulia Sari, Winda; Adilla, Raisa; Syamsir, Syamsir (Jurnal Greenation Sosial dan Politik, 2023)
Abstrak: BAZNAS West Sumatra Province is an official institution established by the government with the task of collecting and distributing zakat, infaq and alms in West Sumatra. In creating quality amil zakat services in West Sumatra Province, BAZNAS management must have a high work ethic in zakat management in West Sumatra. The purpose of this research is to identify, understand, and explain the leadership style applied by BAZNAS of West Sumatra Province, as well as to explain strategies for improving employee work ethic. This study uses a qualitative method. The results of this study are that the leadership style applied by BAZNAS of West Sumatra Province is collective collegial, and the work ethic applied by employees is an Islamic work ethic. In this case the collective collegial leadership style has a relationship with the work ethic, where the collective collegial leadership style will enhance and realize the work ethic through teamwork in realizing the goals of the BAZNAS of West Sumatra Province. Abstrak: BAZNAS Provinsi Sumatra Barat merupakan lembaga resmi yang dibentuk oleh pemerintah dengan tugas menghimpun dan menyalurkan zakat, infaq dan sedekah di Sumatra barat. Dalam menciptakan pelayanan amil zakat yang berkualitas di Provinsi Sumatra Barat, maka pengurus BAZNAS harus memiliki etos kerja yang tinggi dalam pengelolaan zakat di Sumatra Barat. Tujuan penelitian ini untuk mengetahui, memahami, dan menjelaskan gaya kepemiminan yang diterapkan oleh BAZNAS Provinsi Sumatra Barat, serta menjelaskan strategi dalam meningkatkan etos kerja pegawai. Penelitian ini menggunakan metode kualitatif. Hasil dari penelitian ini adalah gaya kepemimpinan yang diterapkan oleh BAZNAS Provinsi Sumatra Barat adalah kolegial kolektif, serta etos kerja yang diterapkan oleh para pegawai adalah etos kerja islami. Dalam hal ini gaya kepemimpinan kolegial kolektif memiliki hubungan dengan etos kerja, di mana gaya kepemimpinan kolegial kolektif akan meningkatkan dan mewujudkan etos kerja melalui kerja sama dalam tim dalam mewujudkan tujuan BAZNAS Provinsi Sumatra Barat.